PENGARUH TINGKAT KEHADIRAN SISWA KELAS XI KE PERPUSTAKAAN TERHADAP LITERASI MEMBACA DI MADRASAH ALIYAH NEGERI 1 SURAKARTA - Indah Nurhidayati; Nurul Meisarah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The purpose of this research is to (1) determine the attendance rate of 11th-grade students at the library in MAN 1 Surakarta, (2) determine the reading literacy level of 11th-grade students at MAN 1 Surakarta, (3) determine the effect of the attendance rate of 11th-grade students at the library on reading literacy at MAN 1 Surakarta. This research uses a quantitative research type with a survey method. The data collection methods used are questionnaires and documentation. To test the hypothesis, statistics were used with simple regression analysis techniques. The population in this study consists of 473 students, and according to Arikunto, 25% of the population can be taken if it exceeds 100 people, so the sample size for this study is 118 respondents, namely 11th-grade students at MAN 1 Surakarta for the 2024/2025 academic year. The research results show that: 1) The attendance rate of 11th-grade students at MAN 1 Surakarta is categorized as